2012
DOI: 10.1021/jp2047135
|View full text |Cite
|
Sign up to set email alerts
|

Co+-Assisted Decomposition of h6-Acetone and d6-Acetone: Acquisition of Reaction Rate Constants and Dynamics of the Dissociative Mechanism

Abstract: Reaction rate constants have been acquired for the gaseous unimolecular decomposition reaction of the Co(+)(OC(CH(3))(2)) cluster ion and its deuterium labeled analog. Each rate constant is measured at a well resolved cluster internal energy within the range 12,300-16,100 cm(-1). The weighted, averaged kinetic isotope effect (KIE), k(H)/k(D) = 1.54 ± 0.05, is about three times smaller than the KIE measured for the rate-determining rate constants in the similar Ni(+)(OC(CH(3))(2)) decomposition reaction. These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…[7][8][9][10][11] Recently, we reported theoretical studies of gas-phase reactions of MS + 2 (M=Sc, Ti, V, Nb) with S-transfer reagents: MS + + COS→MS + 2 + CO. [19][20][21][22] Although the reactions of these cationic sulfides have similar patterns of product distributions, their reactivities and the relevant reaction mechanisms may be different as a result of their different valence-electron numbers and different electronic configurations. For example, a four-membered cyclic transition-state was found in the S-transfer reaction of ScS + with COS, 16 whereas no analogous transition state was found in the reaction of TiS + . 20 Theoretical studies of these reactions are necessary to confirm the relevant mechanisms, but no theoretical studies on the S-transfer reaction of YS + with COS have yet been reported.…”
Section: +Comentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9][10][11] Recently, we reported theoretical studies of gas-phase reactions of MS + 2 (M=Sc, Ti, V, Nb) with S-transfer reagents: MS + + COS→MS + 2 + CO. [19][20][21][22] Although the reactions of these cationic sulfides have similar patterns of product distributions, their reactivities and the relevant reaction mechanisms may be different as a result of their different valence-electron numbers and different electronic configurations. For example, a four-membered cyclic transition-state was found in the S-transfer reaction of ScS + with COS, 16 whereas no analogous transition state was found in the reaction of TiS + . 20 Theoretical studies of these reactions are necessary to confirm the relevant mechanisms, but no theoretical studies on the S-transfer reaction of YS + with COS have yet been reported.…”
Section: +Comentioning
confidence: 99%
“…Transition-metal-ion chemistry is an active area for both experimental and theoretical studies. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] In recent years, Schwarzʹs and Armentroutʹs research groups [7][8][9][10][11] have reported experimental studies of the thermochem-…”
Section: Introductionmentioning
confidence: 99%
“…These rate constants provide mechanistic and dynamic details of the reaction. 58,59 Our goal is to provide accurate data on the catalytic behavior of bare metals with simple substrates such that an intimate knowledge of the actual catalytic capabilities of transition metals can be determined. This inherent catalytic power, once explored for a range of metals and substrates, should provide us with highly detailed information that can be exploited toward a rational design of new catalysts via fine tuning of the aforementioned environmental add-ons (ligands, counterions, solvent, etc.).…”
Section: ■ Introductionmentioning
confidence: 99%
“…The observed KIE is three times smaller than that of Ni + (OC(CH 3 ) 2 ) system. The authors proposed that the unique dissociation dynamics of the two systems are due to the different electronic structure of each atomic ion …”
Section: Introductionmentioning
confidence: 99%
“…The authors proposed that the unique dissociation dynamics of the two systems are due to the different electronic structure of each atomic ion. [29] Although the PES of the Ni + + acetone system was studied, it should be recognized that certain reaction processes can be highly metal specific. The detailed reaction pathways and geometrical parameters of the intermediates involved in the reactions of first-row transition metal monocations with acetone have not been fully explored.…”
Section: Introductionmentioning
confidence: 99%